Characterization of response to atezolizumab + bevacizumab versus sorafenib for hepatocellular carcinoma: Results from the IMbrave150 trial. (29th June 2021) - Salem, Riad; Li, Daneng; Sommer, Nicolas; Hernandez, Sairy; Verret, Wendy; Ding, Beiying; Lencioni, Riccardo
Abstract: Background: IMbrave150 is a phase III trial that assessed atezolizumab + bevacizumab (ATEZO/BEV) versus sorafenib (SOR) in patients with unresectable hepatocellular carcinoma (HCC) and demonstrated a significant improvement in clinical outcomes. Exploratory analyses characterized objective response rate (ORR), depth (DpR), and duration of response (DoR), and patients with a complete response (CR). Methods: Patients were randomized 2:1 to intravenous ATEZO (1200 mg) + BEV (15 mg/kg) every 3 weeks or oral SOR (400 mg) twice daily. Tumors were evaluated using Response Evaluation Criteria in Solid Tumors version 1.1 (RECIST 1.1) and HCC‐modified RECIST (mRECIST). ORR by prior treatment and largest baseline liver lesion size, DoR, time to response (TTR), and complete response (TTCR) were analyzed. Results: For both criteria, responses favored ATEZO/BEV versus SOR regardless of prior treatment and in patients with lesions ≥3 cm. Median TTR was 2.8 months per RECIST 1.1 (range: 1.2–12.3 months) and 2.8 months per mRECIST (range: 1.1–12.3 months) with ATEZO/BEV. Patients receiving ATEZO/BEV had a greater DpR, per both criteria, across baseline liver lesion sizes. Characteristics of complete responders were similar to those of the intent‐to‐treat population. In complete responders receiving ATEZO/BEV per mRECIST versus RECIST 1.1, respectively, median TTCR was shorter (5.5 vs. 7.0 months), mean baseline sum of lesion diameter was longer (5.0 [SD, 5.1] vs. 2.6 [SD, 1.4] cm), and mean largest liver lesion size was larger (4.8 [SD, 4.2] vs. 2.3 [SD,  1.0] cm). Conclusions: These data highlight the improved ORR, DpR, and CR rates with ATEZO/BEV in unresectable HCC. Abstract : IMbrave150 is a randomized phase III trial that showed statistically significant and clinically meaningful improvements in overall survival and progression‐free survival with atezolizumab plus bevacizumab versus sorafenib. The post hoc analyses presented here further highlight the ability of ATEZO/BEV to improve overall response rates, depth of response, and complete response rates in unresectable hepatocellular carcinoma versus sorafenib.